Assessment of acute coronary syndromes among patients with left main coronary artery disease in centers with and without cardiac surgery on-site. Data from PL-ACS registry - Karol Śmiech; Krzysztof Brust; Kamil Bujak; Mariusz Gąsior; Tomasz Roleder (Cardiology Journal)
BACKGROUND: The treatment of left main coronary artery disease (LMCAD) in acute coronary syndrome patients is challenging in daily clinical practice. Therefore, the question arises whether the clinical outcomes of acute coronary syndrome (ACS) patients with LM disease vary between centers with and without cardiac surgery on site. METHODS: The study is a retrospective analysis of ACS patient outcomes using data from the PL-ACS registry, which is a Polish archive of ACS patients. The following analysis considered patients with LMCAD (n=4000) who were divided into two groups: those treated in the centers with the cardiac surgery department on site (CS group, n=427) and those without (non-CS group, n=3573). RESULTS: Patients with ACS in non-CS group more often were not qualified for revascularization than patients in CS group (11.7% in the CS group vs. 19.9% in the non-CS group, p<0.001), however, CABG was more common in non-CS group (18.7% in CS group vs. 25.7% in non-CS group, p<0.001). PCI, including angioplasty of LM, was more common in CS-group than non-CS group (38,6% vs. 30,3%, p<0.001). Among patients with ACS in CS group, major adverse cardiac events (MACE) were observed with greater frequency. CONCLUSIONS: Patients with LM disease admitted to the centers with CS initially had more risk factors for more intensive hospitalization compared to patients in centers without CS on-site. Clinical outcomes and treatment procedures may differ regarding the availability of CS on-site.